2020
DOI: 10.3390/math8122194
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Multiple-Root Finding Iterative Methods Based on Weight Functions

Abstract: A straightforward family of one-point multiple-root iterative methods is introduced. The family is generated using the technique of weight functions. The order of convergence of the family is determined in its convergence analysis, which shows the constraints that the weight function must satisfy to achieve order three. In this sense, a family of iterative methods can be obtained with a suitable design of the weight function. That is, an iterative algorithm that depends on one or more parameters is designed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…The qualitative performance of different iterative schemes designed for solving nonlinear equations with multiple roots has been studied by different authors (see, for example, Reference [17][18][19]). It has been made by using discrete complex dynamics, as all these schemes are without memory.…”
Section: Qualitative Study Of the Proposed Iterative Methods With Memory For Multiple Rootsmentioning
confidence: 99%
“…The qualitative performance of different iterative schemes designed for solving nonlinear equations with multiple roots has been studied by different authors (see, for example, Reference [17][18][19]). It has been made by using discrete complex dynamics, as all these schemes are without memory.…”
Section: Qualitative Study Of the Proposed Iterative Methods With Memory For Multiple Rootsmentioning
confidence: 99%
“…In this paper, we are inspired precisely by this idea, which is to increase the speed of convergence of Steffensen's method while trying not to deteriorate its other characteristics, such as accessibility and efficiency. For this purpose, we have constructed a parametric family of multi-step iterative methods without derivatives, making use of a weight function H(t (k) ) (see [6,8]), which allow us to explore the different advantages of each of the methods that are part of this family depending on the form of this function. The family is described by the following iterative scheme:…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that iterative schemes stable for such functions tend to perform better when applied to more complicated functions than methods exhibiting pathologies. To this end, the tools of complex discrete dynamics are employed to analyze stability in quadratic polynomials (see for example the work of Amat et al in [13,14], Argyros et al in [15], Behl et al in [16], Chicharro et al in [17], Rafiq et al in [18], Kansal et al in [19], Khirallah et al in [20], and Moccari et al in [21], among others).…”
Section: Introduction and Preliminary Conceptsmentioning
confidence: 99%